PERHITUNGAN HARGA POKOK PRODUKSI PADA USAHA MIKRO KECIL MENENGAH (UMKM) TEMPE IBU MURNI DI DESA LANCANG KUNING - Andres Putranta Sitepu; Boyke Aldi Satria; Galuh Maulida Rini; Natasya Sarasafika; Nurlela Sari; Okky Ariandy; Sry Yuliany; Tertia Theola; Waode Irnovadila (Bajang Institute, 2023)
Micro, Small and Medium Enterprises (MSME) is a business that runs in various types of business fields, including trade, agricultural business, industrial business, service business and others. This service aims to analyze the calculation of the cost of goods sold as a basis for determining the selling price of products in determining profits in tempe production. Costs that have been incurred are used as an element of calculation and formation of cost of goods sold and selling price expenses as the basis for determining operating income. The results of community service activities are that the benefits of calculating the cost of production for (MSME) are very important, in addition to helping (MSME) actors in knowing the costs needed and incurred it also helps (MSME) players in knowing product selling prices and monitoring the realization of production costs.